Steep - Obenhaus, Mark; Backstrom, Ingrid; Baud, Anselme; Briggs, Bill, 1931- (Culver City, Calif. : Sony Pictures Home Entertainment, 2008)
Follows the worlds best extreme skiers as they go across the world to find the steepest runs.
Originally released as a motion picture in 2007.
Features: commentary and Q&A with director Mark Obenhaus and skiiers Ingrid Backstrom and Andrew McLean, 2 photo montages, interview with Doug Coombs.
Interviewees: Ingrid Backstrom, Anselme Baud, Bill Briggs, Doug Coombs, Chris Davenport.
DVD, Dolby digital 5.1 surround.
In English with optional English or French subtitles.
Closed-captioned.
Keywords: Skiers; Skis and skiing; Video recordings for the hearing impaired; Nonfiction films; Sports films; Documentary films